Epigenetic Aspects of Chronic Diseases - Roach, Helmtrud I.; Bronner, Felix; Oreffo, Richard O.C.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2011)
Epigenetic Aspects of Chronic Diseases assembles in comprehensive form what is known about the role of epigenetics in chronic disease development. This book provides new insights into treatment, including modulation of epigenetic regulation. Each chapter gives an outline of a respective disease, explains why epigenetics may be involved in the disease process and then presents the evidence of how changes in epigenetic status contribute to initiation and progress of the disease. The final chapters look towards future therapeutic treatment, based on manipulation of epigenetic aspects. Written by widely published experts, Epigenetic Aspects of Chronic Diseases is a valuable reference tool for clinicians and researchers who investigate and treat chronic diseases, as well as health care personnel, post-doctoral fellows and medical or dental students.
Epigenetics and Chronic Diseases: An Overview -- Techniques to Study DNA Methylation and Histone Modification -- Mechanisms of Epigenetic Gene Silencing -- Mechanisms of Epigenetic Gene Activation in Disease: Dynamics of DNA Methylation and Demethylation -- The Role of Histone Demethylases in Disease -- Autoimmune Diseases -- Epigenetics of Rheumatoid Arthritis -- DNA Methylation Changes in Osteoarthritis -- Epigenetics and Type 2 Diabetes -- Epigenetic Regulation of Asthma and Allergic Diseases -- Epigenetics in Psychiatry -- Epigenetics and Late-Onset Alzheimer$1 (Bs Disease -- Epigenetic Mechanisms in the Developmental Origins of Adult Disease -- Targeting Histone Deacetylases in Chronic Obstructive Pulmonary Disease -- Clinical Trials of Epigenetic Modifiers in the Treatment of Myelodysplastic Syndrome.s
Keywords: Medicine; Human genetics; Internal medicine; Biochemistry; Biomedicine; Human Genetics; Medical Biochemistry; Internal Medicine